PARALINGUISTIC FEATURES IN STUDENTS' STORYTELLING WITHIN MULTIMODAL COMMUNICATIONS - Sumekto, Didik Rinan; Dardjito, Hanandyo; Sukur, Silvester Goridus; Andriani, Yunita Susi; Olam, Rismalla Ma'im; Sulistyorini, Dyah Ayu (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2024)
This study assessed paralinguistic features in Indonesian university students' contextual interaction during storytelling. Data collection was recorded from respondents' two video-based storytelling performances, while a self-rated questionnaire was distributed to 235 respondents out of 481 undergraduate English education students using simple random sampling. Data analysis used a mixed-methods approach to qualify students' paralinguistic features using the eduistic linguistics annotator (ELAN) and to quantify the paralinguistic features using statistical analyses through the significance of .05. The findings revealed that the ELAN analyzed the contextual interaction among freshmen, sophomores, juniors, and seniors. The students’ paralinguistic features corresponded with the lexical and semantic evidence, which approached the function of monosyllabic and bisyllabic words, nonverbal expressions, and interpretations. Bodily gesture quantitatively showed moderate category for 44.7% (t = 2.434; p = .016), articulation showed attributable category for 54.0% (t = 3.789; p = .000), facial expression showed moderate category for 61.7% (t = 2.472; p = .014), and voice loudness showed attributable category for 47.7% (t = 4.121; p = .000). Herein, positive and significant attribution were shown by these paralinguistic features towards students' contextual interactions in storytelling for 34.9% with the multiple regressions (F = 7.990, R² = .349, and p < .000). The paralinguistic features empirically address the multimodal communication modes to improve teaching and learning activities.